Comparison of Ivor Lewis and Sweet esophagectomy for middle and lower esophageal squamous cell carcinoma: A systematic review and pooled analysis - Xue, Yuhang (EClinicalMedicine, 2020)
BACKGROUND: Lack of robust evidence highlights the important need to address the controversy on the clinical safety and effectiveness between Ivor Lewis versus Sweet procedure for middle and lower esophageal squamous cell carcinoma (ESCC). METHODS: Search results were filtered according to certain criteria and were analyzed in line with Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. FINDINGS: The inter-study heterogeneity was high. Ivor Lewis procedure might be associated with longer operation time (p < 0.01) and higher lymph node yield (p < 0.01) compared with Sweet procedure. There was no significant difference in the length of hospital stay and postoperative complications with similar reoperation rate between the two procedures (p > 0.05). As the combined analysis of survival data revealed, there was no statistical difference in the oncologic efficacy of them (p = 0.97). INTERPRETATION: The present study based on retrospective data with high heterogeneity indicated that Ivor Lewis esophagectomy might be associated with increased lymph node yield but longer operation time than Sweet. Prospective studies are warranted to compare the long-term survival of Ivor Lewis esophagectomy versus Sweet for middle and lower ESCC.